The Modernist’s Critisism of The Sunnah Through Fabrication – A Critical Study - Klaina, Mekki; Hanane Yachaoui (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This study addresses an important issue concerning the doubts raised by modernist Arab writers regarding the authenticity of the Prophetic Sunnah, particularly their claim that fabricated Hadiths have been mixed with authentic ones. These claims, presented as original ideas by their proponents, are in fact largely based on Orientalist studies. The significance of this study lies in defending the integrity of the Sunnah and demonstrating the methodology developed by Hadith scholars to preserve it. The research aims to explore these claims, trace their origins, and provide a well-grounded response to these assertions. The main challenge is to expose these misconceptions and clarify that the Sunnah has been carefully safeguarded. The study follows a historical, analytical, and critical approach, examining the claims of fabrication, the foundations upon which they are based, their origins, and offering a critique. The key findings reveal that these modern critiques are not based on strong evidence, but rather stem from Orientalist sources, which are generally characterized by a lack of intellectual honesty. Furthermore, the research shows that Hadith scholars meticulously identified and classified fabricated Hadiths, ensuring the integrity of the Sunnah.